2020
DOI: 10.1002/ange.202011604
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Self‐Assembling Small Molecules as Vaccine Adjuvants

Abstract: Immune potentiators, termed adjuvants, trigger early innate immune responses to ensure the generation of robust and long‐lasting adaptive immune responses of vaccines. Presented here is a study that takes advantage of a self‐assembling small‐molecule library for the development of a novel vaccine adjuvant. Cell‐based screening of the library and subsequent structural optimization led to the discovery of a simple, chemically tractable deoxycholate derivative (molecule 6, also named cholicamide) whose well‐defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Notably, the small molecule of cholicamide is distinct from nucleoside deoxycholate derivatives such as imidazoquinolines, but the cholicamide assemblies can bind to the RNA-binding pocket of TLR7. 91 In a subsequent study, the researchers investigated the application of self-assembled cholicamide as an antigen carrier. They found that the assemblies of antigen-cholicamide conjugates with cholicamide could induce high levels of MHC II presentation of antigen peptides and cytokine release.…”
Section: Self-adjuvanting Materials For Tlr Signaling Pathway Activationmentioning
confidence: 99%
“…Notably, the small molecule of cholicamide is distinct from nucleoside deoxycholate derivatives such as imidazoquinolines, but the cholicamide assemblies can bind to the RNA-binding pocket of TLR7. 91 In a subsequent study, the researchers investigated the application of self-assembled cholicamide as an antigen carrier. They found that the assemblies of antigen-cholicamide conjugates with cholicamide could induce high levels of MHC II presentation of antigen peptides and cytokine release.…”
Section: Self-adjuvanting Materials For Tlr Signaling Pathway Activationmentioning
confidence: 99%
“…In this regard, we consider aggregation, a spontaneous phenomenon of hydrophobic molecules in aqueous systems, will be an effective solution to increase tetrazine-chromophore proximity and interactions, enhancing tetrazine quenching effects. [23,53] However, most conventional planar fluorophores suffer from aggregation-caused quenching (ACQ) effect, [54][55][56] which diminishes post-click turn-on emission in aggregates, making it difficult to apply this aggregation strategy for fluorogenic probe designs. Therefore, we focused on aggregation-induced emission luminogens (AIEgens), a series of dyes that exhibit weak emission in dilute solutions but significantly enhanced emission in the aggregate state, to achieve this strategy.…”
Section: Introductionmentioning
confidence: 99%
“…mass spectrometry, liquid chromatography, nuclear magnetic resonance), while drastically minimizing batch-to-batch variations. Leveraging on synthetic building blocks and orthogonal ligation chemistries, unimolecular multicomponent anticancer vaccines can benet from efficient "plug-and-play" design approaches that facilitate in vivo evaluation of various B-cell antigens, 29,30 T-cell epitopes, [31][32][33] adjuvants, [34][35][36] linkers/ spacers, 37,38 and scaffolds. 39,40 Over the last few years, growing attention has been paid to the role of vaccine adjuvants, not only as enhancers but also as "directors" of the immune response.…”
Section: Introductionmentioning
confidence: 99%